Vitamin C Promotes Apoptosis and Cell Cycle Arrest in Oral Squamous Cell Carcinoma - Zhou, Jianjun; Chen, Chen; Chen, Xiaoqing; Fei, Yifan; Jiang, Lei; Wang, Guodong (Frontiers in Oncology, 2020)
Oral squamous cell carcinoma (OSCC) is currently ranked the 8th most pr evalent type of cancer. Despite recent advances in cancer research, the five-yea r survival rate for oral squamous cell carcinoma remains only 50-60%. Therefo re, markers for early detection, identification of efficient chemotherapeutic agent s, and post-therapeutic monitoring are the immediate needs. With this backgrou nd, this study was designed to investigate the anticancer effects of Vitamin C (VC) in oral squamous cell carcinoma. Our results showed that VC had an ant icancer effect on oral squamous cell lines used in this study. VC also showed an inhibitory effect on xenograft tumors in nude mice in vitro and had a syner gistic effect with cisplatin to induce cell apoptosis. Mechanistically, VC caused a significant increase in levels of reactive oxygen species (ROS), which led to induced genotoxic (DNA damage) and metabolic (ATP depletion) stresses, and inhibited Bcl-2 expression and promoted Bax expression and caspase-3 cleavag e. VC also caused cell cycle arrest at the G0/G1 phase in OSCC cells, which is related to the activation of the tumor suppressor p53 and cyclin-dependent k inase inhibitor p21. In conclusion, VC bears considerable therapeutic potential f or the treatment of oral squamous cell carcinoma.